2021
DOI: 10.3390/biomedicines9060614
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Endothelial Function in Convalescent COVID-19 Patients Undergoing Multidisciplinary Pulmonary Rehabilitation

Abstract: Background: Growing evidence points to a key role of endothelial dysfunction in the pathogenesis of COVID-19. In this study, we evaluated changes in endothelium-dependent flow-mediated dilation (FMD) in a cohort of convalescent COVID-19 patients undergoing pulmonary rehabilitation (PR). Methods: After swab test negativization, convalescent COVID-19 patients referring to a post-acute care facility for PR were consecutively screened for inclusion. Study procedures were performed at the time of hospitalization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…The literature evidence of a better prognosis and a lower incidence of CV outcomes among female COVID-19 patients is consistent with the latter result [59,60]. Finally, in line with the previous evidence of a direct and persistent correlation between the severity of pulmonary and vascular disease in this clinical setting [30], we also found that FMD values directly correlated with pulmonary function tests in our post-COVID-19 population. Of particular interest is the correlation between FMD and DLCO%, which may be justified by the functional and structural role of the endothelium within the alveolar-capillary barrier [61].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The literature evidence of a better prognosis and a lower incidence of CV outcomes among female COVID-19 patients is consistent with the latter result [59,60]. Finally, in line with the previous evidence of a direct and persistent correlation between the severity of pulmonary and vascular disease in this clinical setting [30], we also found that FMD values directly correlated with pulmonary function tests in our post-COVID-19 population. Of particular interest is the correlation between FMD and DLCO%, which may be justified by the functional and structural role of the endothelium within the alveolar-capillary barrier [61].…”
Section: Discussionsupporting
confidence: 92%
“…A high incidence of stroke and thromboembolic complications has been reported during the acute phase [39,40], with the risk of arrhythmic and ischemic complications [41][42][43] and subsequent hemodynamic instability [44,45]. Moreover, it has been suggested that such increased CV risk may persist during convalescence [30], as confirmed by the evidence of magnetic resonance and echocardiographic alterations [41,46] with a non-negligible incidence of venous and arterial thrombotic events [47]. However, the physiopathology of these manifestations has not been fully elucidated [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate for the first time elevated SDC-1 levels as an indication of persistent impairment of glycocalyx after COVID-19 infection with mild disease progression without hospitalization. These results support the work of Ambrosino et al on hospitalized convalescent COVID-19 patients 2 months after severe or critical disease progression (WHO classification III/IV), in whom sex-dependent signs of endothelial damage were also found [24,25]. The study population, especially females, had significantly decreased endothelium-dependent flow-mediated dilation (FMD) compared with matched controls (demographics, previous disease).…”
Section: Discussionsupporting
confidence: 89%